AFLATOXINS CONTAMINATION IN NNAM OWONDO (A LOCAL GROUNDNUT-BASED FOOD), AND CONSUMERS’ DIETARY EXPOSURES AND SAFETY LEVELS IN YAOUNDE, CENTRE REGION OF CAMEROON - Marchel A. ASENECK; Hippolyte T. MOUAFO; Angele TCHANA; Sidiki C. DIMALA; Hassan A. KAMAL; Oluwatobi KOLAWOLE; Wilfred A. ABIA (Food and Environment Safety, 2024)
This study aimed to assess total aflatoxins (AFT) dietary exposure levels and the associated health risk amongst ‘Nnam owondo’ (NO) consumers (adults and children) in Yaounde, Cameroon. A survey on NO consumption practices and consumers’ knowledge of aflatoxins was conducted using a structured food frequency questionnaire. ‘NO’ samples together with 5 laboratory-simulated traditional (ST) and 6 simulated modified traditional (SMT) NO samples, were analyzed for AFT using an ELISA kit. The aflatoxins' health risk was determined using the Margin of Exposure (MOE) and quantitative liver cancer risk approach. Adults and children in this study consume on average 122.5 and 99.6 g of NO daily respectively, 2-3 times per week. All pooled samples were contaminated with AFT (mean: 17.2; range: 5.41-34.02 µg/Kg). Around 62.5% (20/32) of pooled NO samples had AFT levels that exceeded the regulatory limit of 10 µg/Kg established by the Food and Agriculture Organization for groundnut-based foods intended for direct human consumption. Mean daily exposures (MOE) of the pooled samples were 0.03 (13.02) and 0.04 (9.98) µg/Kg bw/day for adults and children respectively. A mean cancer risk range: 6 to 10 cancer cases per year per 100,000 populations were observed for children and adults in this study. Application of the SMT led to a 62.2 % reduction in AFT level when compared to ST, with a corresponding decrease in MOE to 0.011 (36.36) and 0.014 µg/Kg bw/day (28.57) for adults and children, respectively, although the AFT dietary exposure remains a public health treat.